Of benevolent Gods and Imperfect Worlds - Ojeda Couchoud, Santiago (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
The term «Theodicy» was coined by Leibnitz at the beginning of the Enlightenment and it designates since then the Theists’ attempts to justify their idea of a benevolent, omnipotent God interested in his creation but confronted with the stubborn, undeniable reality of evil. That justification seems to us now necessarily etiological, although equally fruitful and relevant to our own time: The present work attempts to reveal succinctly the socio cultural conditions apparent in the most relevant etiologies formulated after Leibnitz, and their parallelism with the ones current today. Starting from that parallelism we will point to the likely features of a modern Theodicy, using the premises of analytic philosophy and philosophical theology, centered around the different types of evil and the understanding of world and mind that may pave the way to potential solutions.
Keywords: Theodicy; analytic Philosophy; enlightenment; philosophical Theology